The impact of digital competence, organizational culture, and work flexibility on employee productivity with job satisfaction as a moderation variable - Fauzi, Rian; Suhardi, Suhardi; Firdaus, Rahmad (Trigin Publisher, 2025)
This study aims to analyze the influence of organizational culture, work flexibility, and digital competence on work productivity and job satisfaction. The respondents in this study were 200 respondents who were employees working in various industrial sectors in Bangka Belitung who experienced digital transformation in their work environment, Using the path analysis method, the results of the study showed that organizational culture has a positive and significant influence on work productivity and job satisfaction. Work flexibility has also been shown to contribute significantly to Job Satisfaction, showing that the higher the flexibility in the work environment, the more employee satisfaction increases. However, digital competencies do not have a significant relationship with Work Productivity, which indicates that competitive factors in the work environment do not necessarily drive increased productivity. These findings contribute to the development of theories in human resource management by emphasizing the importance of organizational culture and work flexibility in increasing employee productivity and satisfaction. Practically, the results of this research can be a reference for organizations to create a more collaborative and flexible work environment to improve employee welfare and performance. However, this study has limitations in sample coverage and does not consider moderator or mediator variables that can affect the relationship between variables. Therefore, future research is suggested to explore additional factors, such as management support and work-life balance, for a more comprehensive understanding of organizational dynamics and employee productivity.